The Effect of Age at Immigration on the Earnings of Immigrants: Estimates from a two-stage model - Dong, Chang (Université d'Ottawa | University of Ottawa, 2016)
Using microdata from the 2006 Canadian Census and the 2011 Canadian National Household Survey (NHS), this paper analyzes the relationship between age at immigration and immigrant wages with a two-stage regression model initially proposed by Schaafsma and Sweetman (2001). By estimating that model for males and females in three different specifications with different control variables, I find a general negative effect of age at immigration on both male and female immigrant wages. The older the immigrant arrived, the lower the wages. However, the ages at immigration between 25 and 34 for males are an exception. Male immigrants who landed in Canada in those prime working ages perform better than those who immigrated younger or older.